De-aluminated metakaolin-cement composite modified with commercial titania as a new green building material for gamma-ray shielding applications. (December 2022) - Ramadan, M.; Kohail, Mohamed; Abadel, Aref A.; Alharbi, Yousef R.; Tuladhar, Rabin; Mohsen, Alaa
Abstract: Sustainable disposal of dealuminated metakaolin (DAK) is a crucial environmental issue for the alum production industry. In previous studies, DAK was utilized as eco-friendly cementitious materials, but only 10 wt% was used instead of cement as DAK's high percentage has a detrimental effect on the mechanical properties, so the environmental problem of DAK has not yet been solved. In this study, commercial titanium oxide (TiO2 ) was incorporated in a cement matrix containing DAK that reached 50 wt% to benefit from TiO2 's properties in enhancing the mechanical performance of binding materials and producing cementitious blends used as blocking materials against harmful gamma radiation. Five pastes were prepared to reach the main target; ordinary Portland cement (OPC), OPC-10%DAK (D10), OPC-30%DAK (D30), OPC-50%DAK (D50) and OPC-45%DAK-5%TiO2 (D45-T5). By means of a mini-slump test, all fresh blends have very close flowability using the appreciated additions of polycarboxylate superplasticizer. The hardened composites were cured in tap water for up to 28-days. Compressive strength results at 28 days for OPC, D10, D30 and D50 were 80, 94.6, 60.8 and 57.6 MPa, respectively. An obvious turning point in strength value from 57.6 to 88 MPa after replacement of DAK by 5 wt% TiO2 (D45-T5). A gamma-ray shielding test was performed using two radioactive isotopes (Co-60 and Cs-137). The inclusion of 5% TiO2 has a great impact on the development of shielding power of D45-T5 compared with OPC; the linear attenuation coefficient (µ) values were enhanced from 0.127 ± 0.003 cm −1 to 0.199 ± 0.007 cm −1 at 661.6 Kev and from 0.118 ± 0.003 cm −1 to 0.144 ± 0.005 cm −1 at 1332.5 Kev. The unique properties of specimens containing the anatase phase may be attributed to the fact that the TiO2 may act as a nano-filler and active seeds for the formation of further hydration products such as CSHs, CAHs and CASHs as detected by X-ray diffraction (XRD), thermal analyses techniques (TGA/DSC) and scanning electron microscope (SEM/EDX). TiO2 caused rearrangement of the textural structure of D45-T5 composite to meso pores, as proved by N2 -adsorption/desorption technique. Moreover, the TiO2 's tetragonal structure makes it has dosimetric characteristics of high adsorbent for gamma rays. Highlights: Mechanical and textural characteristics for DAK-blended cement paste. Radiation shielding efficiency for DAK-blended cement paste modified with TiO2. TiO2 has a great return on the strength values for DAK-blended cement paste. OPC-DAK-TiO2 composite has high efficiency in shielding gamma-rays. TiO2 has a vital role in textural characteristics rearrangement.